Pengaruh Inovasi terhadap Kinerja Pemerintah Daerah dan Implikasinya pada Kualitas Pelayanan Publik di Kabupaten Labuhanbatu Selatan Provinsi Sumatera Utara - Zulkifli Zulkifli (Institut Pemerintahan Dalam Negeri (IPDN), 2020)
This research aims to describes and analyze the influence of innovation to local government performance and its implications to public service quality. This reasearch also uses quantitative approach in positivist paradigm with using LISREL version 8.8 to managing the data. All informants are gathered from slovin formula and analyzed with several secondary data. Reseach result shows that innovation variable significantly influenced local government performance, and local government performance significantly influenced public service quality. Some recommendations are suggested namely innovation policy from local government should be socialized to citizens in order to increasing public awareness.